2019
DOI: 10.3390/rs11232805
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Long-Term Moon-Based Observation Characteristics for Arctic and Antarctic

Abstract: The Antarctic and Arctic have always been critical areas of earth science research and are sensitive to global climate change. Global climate change exhibits diversity characteristics on both temporal and spatial scales. Since the Moon-based earth observation platform could provide large-scale, multi-angle, and long-term measurements complementary to the satellite-based Earth observation data, it is necessary to study the observation characteristics of this new platform. With deepening understanding of Moon-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…This contrasts with Ren et al [20] and Ye et al [21], whose geometry models do not consider the effects of minimum elevation angle to the spatial coverage, and the positions of their Moon-based sensor satisfy the condition of observing one point on the Earth rather than the entire hemisphere of the Earth. In addition, Wang et al [34] and Sui et al [35] also discusses the observation characteristics of a Moon-based platform, but they concentrate on the polar regions and Moon-based sensors located in certain places; thus, the two distinct lines as shown in Figure 7 are not found in their study. Our work focuses on Earth hemispheric observations, including polar regions, and sensors anywhere on the lunar intervisible spherical cap can achieve hemispheric observations.…”
Section: Discussionmentioning
confidence: 99%
“…This contrasts with Ren et al [20] and Ye et al [21], whose geometry models do not consider the effects of minimum elevation angle to the spatial coverage, and the positions of their Moon-based sensor satisfy the condition of observing one point on the Earth rather than the entire hemisphere of the Earth. In addition, Wang et al [34] and Sui et al [35] also discusses the observation characteristics of a Moon-based platform, but they concentrate on the polar regions and Moon-based sensors located in certain places; thus, the two distinct lines as shown in Figure 7 are not found in their study. Our work focuses on Earth hemispheric observations, including polar regions, and sensors anywhere on the lunar intervisible spherical cap can achieve hemispheric observations.…”
Section: Discussionmentioning
confidence: 99%
“…For a DEM grid, the azimuth angle of the surrounding point k to the center point O in MSC is expressed as ϑ k in Equation (7).…”
Section: Sunlight Time Coveragementioning
confidence: 99%
“…Existing studies have revealed that Moon-based Earth observation provides longevity, integrity, and stability advantages over satellites in observing the solid Earth tide, global energy budget, climate and environmental change, and even the near-Earth space environment [5,6]. Furthermore, Moon-based Earth observation is unique in its ability to monitor phenomena related to Earth-Moon interaction [7,8]. Due to the advantages and uniqueness of Moon-based Earth observation, a broadband radiometer and an array spectrometer will be settled on the lunar surface to conduct a long-term Earth radiation budget experiment in this decade [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Various types of earth observation satellites, space stations, deep space probes, and other artificial equipment have been successfully launched into international space since the 1960s, and a number of satellite earth observation programs have been implemented [5]. Climate change, resource and environmental change detection, and disaster risk reduction and prevention have all benefited from the use of aviation and aerospace earth observation applications.…”
Section: Earth Observation Programsmentioning
confidence: 99%